Colloquium in Teaching Library Science - Gopinath, M. A.; Neelameghan, A. (Journal of Information and Knowledge, 1966)
Weekly Colloquium is a multi-purpose institution. The teacher and students should participate in the behind-the-screenwork such as, compilation of a bibliography, selection of office-bearers, choice of subject, framing of propositions, and reporting. The colloquium trains the student in free systematic thinking, in clear exposition, and in healthy productive team-work.